The Effects of Green Financing, Firm Size, and Operating Income on Bank Firm Value - Vinatya Ayu Natasya; , Omi Pramiana (Proceeding International Conference on Digital Education and Social Science, 2025)
This study examines the effect of green financing, firm size, and operating income on firm value in banking companies listed on the Indonesia Stock Exchange (IDX) for the period 2022–2024. Using a quantitative approach, secondary data were collected from annual reports, sustainability reports, and financial reports. Multiple linear regression analysis was performed using SPSS. The results show that green financing, firm size, and operating income each have a positive and significant effect on firm value. The regression model produced an R-square value of 0.944, indicating that the three independent variables together can explain 94.4% of the variation in firm value. All hypotheses were supported, confirming the importance of sustainable financing and strong operational performance in increasing firm value. These findings contribute theoretically to the literature on sustainable finance and provide practical insights for banking management and investors.